(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In this article, the socio philosophical views of Abai in theoretical manner are considered in detail.It revolves the secrets of perceptional ideas and the rationalism of Abai. According to Abai, the man is not born as clever or stupid, virtuous or villain. It is embodied with the work and upbringing. Abai is the great thinker who deeply has learnt the logical perception. Keywords: philosophical look, wise man, rational cognition, education, labour.